Playing Her Story: Gender Negotiation, Cultural Memory, and Players’ Engagement in Code: Kite - Ma,Yixin (2025)
This study explores the interplay between gender, gaming, and cultural memory through the case of Code: Kite, a Chinese female-oriented historical game that reimagines the Three Kingdoms era from a female perspective. Drawing on semi-structured interviews with eleven female players and analyzed through thematic analysis, the research examines how players perceive gender expression in the game, how their engagement with game narratives contributes to the construction of cultural memory, and how postfeminism offers alternative frameworks for interpreting gender and agency in digital play. The findings reveal that players do not passively consume media texts but actively negotiate meanings through emotional, cognitive, and creative engagement. Their interpretations of both romantic and non-romantic narratives demonstrate nuanced critiques of traditional gender norms and reveal a desire for empowered and multifaceted representations of femininity. Simultaneously, the players rework historical knowledge through affective investment and narrative reinterpretation, forming what this study terms a gendered gaming memory, a process wherein gendered experience and historical imagination are co-produced through gameplay. The study contributes to emerging research on gendered memory by foregrounding games as sites of memory-making. It also adopts a reflexive use of postfeminist theory, acknowledging its critiques while highlighting its relevance in explaining how women enact agency within consumerist and media-saturated environments. By centering female players' voices, this research sheds light on the affective, critical, and at times resistant ways in which women engage with history and gender politics in contemporary Chinese game culture.
Keywords: Cultural memory; Gender Representation; Postfeminism; Media Engagement; Digital Games